Development of 4.5 keV monochromatic X-ray radiography using the high-energy, picosecond LFEX laser. (May 2016) - Sawada, H; Fujioka, S; Hosoda, T; Zhang, Z; Arikawa, Y; Nagatomo, H; Nishimura, H; Sunahara, A; Theobald, W; Patel, P K; Beg, F N
Abstract: Development of a monochromatic x-ray imaging system using a high-energy short- pulse laser LFEX and a spherical crystal is reported. Irradiation of the intense short-pulse laser produces a flash of 4.51 keV Ti K-alpha x-ray while the spherically bent quartz crystal provides a narrow spectral bandwidth and high spatial resolution. This high spatiotemporal imaging technique was applied for recording 2-D monochromatic x-ray images of laser-driven Fast Ignition targets. The results show a sufficiently high spatial resolution to characterize the implosion core, suggesting that the core information extracted from the radiograph images can be used to benchmark a 2-D radiation-hydrodynamic code for accurate hydrodynamic modelling and optimization of FI fuel assembly in the asymmetrical implosion.